Pengembangan LKS Pembelajaran Fisika Dengan Menggunakan Model CLIS (Children Learning In Science) Di SMP 1 Muhammadiyah Banjarmasin - Sari, Norma; Annur, Syubhan; Mahardika, Andi Ichsan (Berkala Ilmiah Pendidikan Fisika, 2017)
Student worksheet that used on learning activity in SMP 1 Muhammadiyah Banjarmasin is still boring handout. So, this makes students be lazy to understanding physics concept. So, because of that used development reserach on studentwork sheet on physics learning use (Children Learning in Science) is worthy. Especially this research purpose to describe : (1) the validity of student worksheet is developed, (2) the practically of student worksheet is developed, (3) The evectiveness of student work sheet is developed. This research refers to development model of Kemp. The sample that we got from validation sheet of student sheetwork; RPP; THB, observation sheet of RPP, and the result of student learning outcomes sample. Sample has anylized by quantitative and qualitative descriptive. The results of this research is: (1) Student worksheet that developed is stated by valid with few revition by two validators, (2) Student work sheet is stated practice by RPP implementation with very good category, (3) Student worksheet is developed is efective and it is from gain score with medium category. We can conclude is development of student worksheet on physics learning use model CLIS in SMP 1 Muhammadiyah Banjarmasin is stated worthy to used, because it is fulfill with valid, practical and efective category.